Analyses of the oil industry and its impact on the economy of the Republic of Kazakhstan - Bugubayeva, R.O.; Zhetpisbayeva, M.K.; Gimranova, G.I.; Abdikarimova, A.T.; Bespayeva, R.S. (BUKETOV BUSINESS REVIEW, 2019)
The oil and gas industry of the Republic of Kazakhstan is of strategic importance for the development of the Republic of Kazakhstan. Over the years, the industry has shown high growth rates of production, an increase in the share of GDP of Kazakhstan. However, we can not say that this industry has a great multiplier effect in the development of the national economy. There are many bottlenecks, including in terms of increasing the «local content» in the oil industry of Kazakhstan. Domestic enterprises and firms are not sufficiently integrated into the production process of oil and gas companies, are not represented among the suppliers of necessary products. The oil and gas industry has not become a «growth point» for the economy of Kazakhstan. The article analyzes the specifics of the modern oil and gas sector of the Republic of Kazakhstan in the context of globalization processes in the world economy, assesses the development of the oil and gas sector and its contribution to the macroeconomic indicators of the national economy. The importance of the oil and gas sector in the development of the processing industry of Kazakhstan and the problem of increasing the local content in the product of the oil and gas industry of Kazakhstan is studied.